Degradasi Tanah Lahan Suboptimal oleh Bacillus mycoides Indigenous dan Kinetika Reaksinya - Zainal Fanani; Bambang Yudhono; Veriana Romarito Situmorang (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
Research about degradation soil of suboptimal land from Lilin River PERTAMINA Musi Banyuasin Regency, South Sumatera have been done. The aim of this research is knowing the capability of Bacillus mycoides on degradation petroleum hydrocarbon. The measurement of first sludge TPH was 71.1567%. First TPH was become more liquid than before on 5; 7.5; 10; 12.5 and 15% with fresh soil, bulking agent and Bacillus mycoides was added 10% from medium total weight. Incubation for 14 days gives result decreasing TPH on each medium become 2.3679; 4.5123; 5.9070; 6.0223 and 8.0010% which is first order reaction. Medium 10% on incubation day 14th; 17th; 22nd; 26th and 31st. On continue, decreasing TPH is 5.9070; 4.5970; 4.0463; 3.7230 and 3.29% with constant rate reaction on 0.0361 /day. GC-MS result sample analysis shows that Bacillus mycoides have an ability to degradation C19H40; C21H44; C24H50 and C28H58 with percentage of concentrate decreasing from those compound is 99.32%.